Pelatihan Analisis Regresi Linear Sederhana Menggunakan Aplikasi IBM SPSS di Politeknik Penerbangan Palembang - Yuniar, Dwi Candra; Febiyanti, Herlina; Nugraha, Minulya Eska; Putra, Bambang Wijaya; Pranata, Andika Dwi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
This training focused on improving the ability of simple linear regression analysis using IBM SPSS application. The training was held on 11 September 2024 at Palembang Aviation Polytechnic and involved 12 students from outside Palembang Aviation Polytechnic. This training aims to provide in-depth insight into how to use IBM SPSS. in simple linear regression analysis. The flow of training implementation consists of initial tests, material, practice, final tea, report writing and publication. The average score of the initial test was 33.33. The final test results showed an average score of 75.83. N-gain score analysis showed 66.67% of participants were in the medium category and 33.33% of participants were in the high category. Based on the paired sample test, the results showed that there was an increase between before and after participating in the training. This training succeeded in increasing understanding and knowledge related to simple linear regression analysis with IBM SPSS.